(untitled) (Research in Agriculture Livestock and Fisheries, 2025)
Beetroot (Beta vulgaris L.) is a highly nutritious root vegetable with great potential for enhancing dietary diversity, wider adaptation, and intensification in Bangladesh. An experiment was conducted at Horticulture Farm, Bangladesh Agricultural University, Mymensingh, from October 2023 to March 2024 to assess the effects of varieties and organic mulching on the growth, yield, and quality of beetroot. It comprised two varieties: Heart Beet (V1) and Red Baby (V2), and four mulches: T0 (control), T1 (rice straw), T2 (water hyacinth), and T3 (leaf mulch). A randomized complete block design (RCBD) with three replications was used to measure plant height, leaf count, root length, root diameter, fresh weight, yield, and total soluble solids (TSS). Significant varietal and mulching effects were observed for all parameters studied. Red Baby (V2) performed better than Heart Beet (V1) in terms of root diameter (3.81 cm versus 3.46 cm), fresh weight (42.01 g versus 34.52 g), and yield (4.14 t/ha against 3.48 t/ha). In contrast, Heart Beet (V1) exhibited a total soluble solids (TSS) level of 16.63 °brix, indicating a greater processing potential. Among the mulches, leaf mulch (T3) produced the best results, with the longest roots (4.15 cm), largest diameter (3.93 cm), highest fresh weight (47.34 g), and greatest yield (4.70 t/ha). The interaction of Red Baby with leaf mulch (V2T3) produced the highest root yield (4.89 t/ha), highlighting a strong synergistic benefit. Res. Agric. Livest. Fish. Vol. 12, No. 3, December 2025: 367-377